ANALISIS EFISIENSI BIAYA PRODUKSI DALAM MENINGKATKAN LABA PADA PT. ARVIS SANADA SANNI INDONESIA - Muda, Rangga Putra; Sembiring, Masta (Worksheet : Jurnal Akuntansi, 2025)
This research aims to analyze the cost efficiency of production in increasing profits at PT. Arvis Sanada Sanni Indonesia. Cost efficiency is a crucial factor in determining a company’s profitability, especially in the competitive coffee export industry. This study uses a descriptive method with a qualitative approach and a case study design. Data were obtained through financial report documentation and interviews with the finance and production departments. The study analyzes data from 2019 to 2023 to examine the relationship between production costs, sales, and operating profit. The findings show that in 2023, although production volume increased, the company experienced significant losses. This was due to inefficiencies in managing production costs that were not accompanied by an increase in sales. Efficiency ratio analysis indicates a significant gap between actual costs and budgeted costs. The conclusion of this study is that suboptimal cost control negatively impacts the company’s profitability. Therefore, it is necessary for the company to implement stricter cost control strategies and optimize production resources to improve efficiency and competitiveness in the global market.